Biomarkers and aging. (June 2014) - Imbert, Isabelle
Biomarkers and Ageing 25 February 2014, London, UK This conference was organized by Euroscicon and was part of the 2014 Ageing Summit. The central theme was biomarkers and aging including current research on biomarkers at the genomics and proteomics level. The informal atmosphere of the conference promoted interaction and networking opportunities between key leaders from industry, academic and clinics. Presentations as well as the discussion panel session brought opportunities to widely discuss the relevance of biomarkers as signatures for human aging or age-related diseases. The meeting highlighted the importance of genomics and regulatory elements in aging, their probable role in successful aging and their potential interest for future antiaging approaches. The meeting was chaired by David Melzer and Lorna Harries (University of Exeter, UK).